Continuing education in Oral Medicine and Oral and Maxillofacial Pathology: a Brazilian regional experience - Souza, Fabrício Tinôco Alvim de; Fonseca, Felipe Paiva; Aguiar, Maria Cássia Ferreira; Aquino, Sibele Nascimento de; Pêgo, Sabina Pena Borges; Guimarães, André Luiz Sena; Reis, Leonardo Amaral dos; Dias, Livia Maris Ribeiro Paranaiba; Cardoso, Sérgio Vitorino; Cordeiro, Mirna Scalon; et al. (Journal of Oral Diagnosis, 2025)
Objective: The objective of this study is to evaluate the outcomes of the continuing education program in Oral Medicine and Oral and Maxillofacial Pathology, from December 2021 to April 2024. Methods: The program, conducted virtually via Google Meet®, aimed to enhance the professional development of dental practitioners in the state of Minas Gerais. Results: A total of ten events were held, attracting over 2,300 participants, including general dentists, dental students, and oral health technicians. The topics covered ranged from clinical case discussions to the diagnosis and treatment of oral diseases, with a particular focus on oral cancer. The study assessed participant engagement through metrics such as attendance and participation in discussions. In addition to the educational events, two awards were established: the "Professor Edgard Carvalho Silva" award, which recognizes outstanding projects in the field of Oral Medicine and Oral Pathology, and the "Carlos Roberto Martins" award, which honors exceptional professionals for their achievements in teaching and research.These initiatives successfully promoted lifelong learning and motivated professionals to advance in their respective fields. Conclusion: The findings indicate that educational program played a pivotal role in addressing the professional needs of the dental community, offering accessible, cost-free education, and fostering greater awareness and excellence in Oral Medicine and Oral and Maxillofacial Pathology throughout Minas Gerais.